2017
DOI: 10.1099/jmm.0.000494
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of diacetylcurcumin against Staphylococcus aureus results in decreased biofilm and cellular adhesion

Abstract: These findings open new avenues for the study of this curcumin derivative as an excellent prototype with anti-MRSA activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Here, we designed and synthesized four alkyl gallate derivatives (the acetylated alkyl gallates 8a-11a) identified as new chemical entities, which also inhibited the phytopathogen X. citri, but exhibited greater potency than their prototypes. Our data are in line with reports from other groups showing that acetylated derivatives can improve potency when compared to their starting compounds (Biasutto et al 2007;Sardi et al 2017;Vlachogianni et al 2015). The conversion of functional groups, known as drug latentiation, results in increased lipophilicity that may be related to greater capacity of penetration into biomembranes (Ettmayer et al 2004;Han and Amidon 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we designed and synthesized four alkyl gallate derivatives (the acetylated alkyl gallates 8a-11a) identified as new chemical entities, which also inhibited the phytopathogen X. citri, but exhibited greater potency than their prototypes. Our data are in line with reports from other groups showing that acetylated derivatives can improve potency when compared to their starting compounds (Biasutto et al 2007;Sardi et al 2017;Vlachogianni et al 2015). The conversion of functional groups, known as drug latentiation, results in increased lipophilicity that may be related to greater capacity of penetration into biomembranes (Ettmayer et al 2004;Han and Amidon 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The ester group is the main alternative to the carboxyl and hydroxyl polar groups, due to the increase of lipophilicity and thus the biomembrane permeability (Beaumont et al 2003;Rautio et al 2008). Previous studies performed by Sardi et al (2017) demonstrated that an acetylated derivative of curcumin, a natural polyphenolic compound, was more potent than its natural prototype against Staphylococcus aureus strains, showing the importance of converting hydroxyl to ester groups for antibacterial activity. Here we demonstrate that acetylation of some of the previously described alkyl gallates increased 100% their potency against X. citri.…”
Section: Introductionmentioning
confidence: 99%
“…The infection development model employs larval caterpillars (third-or final-instar stage) that are injected with bacteria in the hemocoel via the last left proleg (285). The wax moth has (i) facilitated screening of a U.S. Food and Drug Administration-approved library to identify antibiofilm compounds against Francisella novicida (286); (ii) been used to model biofilm formation by Acinetobacter baumannii, Burkholderia cepacia, Burkholderia multivorans, Campylobacter spp., and species in polymicrobial infections, such as the P. aeruginosa Liverpool epidemic strain and oral streptococci (287)(288)(289)(290)(291)(292); and (iii) been applied for evaluation of the antibacterial and antibiofilm activities of alternative therapeutic strategies against a multitude of pathogens, including S. aureus, MSSA, MRSA, and Acinetobacter baumannii (293)(294)(295).…”
Section: Nonvertebrate Animal Modelsmentioning
confidence: 99%
“…In fact, one of their most promising features was the inhibitory effect exerted on Staphylococcus aureus, including methicillin-resistant Staphylococcus aureus (MRSA). The latter is a major cause of nosocomial infections (Dakheel et al 2016) and its incidence has been on the rise, becoming a growing public health concern, especially due to its resistance to a wide range of antibiotic treatment (Sardi et al 2017;Neopane et al 2018). Although antimicrobial activity of EPS has been studied against different pathogenic strains, their effectiveness against MRSA has not been widely investigated.…”
Section: Discussionmentioning
confidence: 99%